2015
DOI: 10.4025/actascianimsci.v37i3.26890
|View full text |Cite
|
Sign up to set email alerts
|

<b>Urea and salt as supplementary diet for crossbreed milk cows

Abstract: This study aimed to evaluate the use of supplementary feed with different percentages of urea and mineral salt for crossbred milk cows. Ten animals were used, mean body weight 480 kg ± 9,7, distributed in a 5 x 5 double Latin square, with treatments of supplements with different urea and mineral salt percentages, namely, 10:10; 10:20; 20:10 and 20:20, completed to 100% with corn meal. Data underwent statistical analysis by SAS at 0.05 significance level. The use of supplements increased (p < 0.05) the total dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…No differences were found (p > 0.05) in milk composition between the studied treatments (Table 4). These results were also observed by Aguiar et al (2013), Souza et al (2015) and Teixeira et al (2015), in investigations with urea addition to sugarcane. Jesus et al (2012) found higher fat content.…”
Section: Resultssupporting
confidence: 75%
“…No differences were found (p > 0.05) in milk composition between the studied treatments (Table 4). These results were also observed by Aguiar et al (2013), Souza et al (2015) and Teixeira et al (2015), in investigations with urea addition to sugarcane. Jesus et al (2012) found higher fat content.…”
Section: Resultssupporting
confidence: 75%
“…Therefore, in the present study, urea from nitrogen salt was not efficiently used in ruminal microbial protein synthesis, which caused a reduced nitrogen balance, probably due to the energy deficit of tropical pasture. Accordingly, Teixeira et al (2015) also found high values of urinary urea nitrogen in dairy cows consuming mineral supplements containing 20% urea (621 to 764 mg dL -1 ). On the other hand, when the concentrate was used in a higher level, the input of energy favored the synthesis of ruminal microbial protein, justifying the increase in total nitrogen excreted in milk.…”
Section: Resultsmentioning
confidence: 82%
“…In the present study, values varied between 13.3 and 14.3 mg dL -1 (Table 2), within the range considered desirable, and without treatment effect. On the other hand, Teixeira et al (2015) found high values of SUN and MUN in dairy cows consuming mineral supplements containing 20% urea (18 to 20 and 20 to 22 mg dL -1 , respectively); and Souza Júnior et al (2016) found high NUS values in dairy cow diets with 16 versus 12% crude protein (27.9 vs 15.0 mg dL -1 ).…”
Section: Resultsmentioning
confidence: 98%
“…Nellore cows have an increase in fat and protein rates as gene fractions of Holstein strain decrease (Teixeira et al, 2015). In current analysis, fat percentage averaged 4.73%, but mean fat percentage in the milk of pure Holstein cows was 3.66% (Aikman, Reynolds, Beever, 2007).…”
Section: Resultsmentioning
confidence: 99%